Analysis of fetal renal cortex development: Cortical maturation index as a new potential guide in fetal renal cortex assessment - Andrejić-Višnjić Bojana; Petrović Ivan; Balenović Ana; Milosavljević Isidora; Petković Jovana; Trivunić-Dajko Sandra; Bosanac Milana; Jeremić Dimitrije; Šunjević Milena (Vojnosanitetski Pregled)
Background/Aim. To date, most of the scientific attention has been aimed at the morphometric analysis of the nephrogenic zone (NZ) of the fetal renal cortex, while the quantification and analysis of the maturation zone (MZ) and other indicators of renal maturity were missing. The aim of the study was to examine the characteristics of fetal kidney cortex maturation, as well as to propose the development of a new cortical maturity index (CMI). Methods. The study included 42 paraffin molds of the fetal kidney, divided into three groups according to gestational age (GA). After hematoxylin and eosin staining, tissue sections were analyzed through the following parameters: the thickness of the NZ and MZ, the renal corpuscles area (RCa) and the glomerular capillary tuft area (GCTa), and the maturation stages of the glomeruli. In addition, a new parameter, CMI, was formed as a ratio of NZ and MZ thickness. The collected data were statistically processed. Results. Changes in NZ and MZ thickness were statistically significant, and they correlated with GA. A value of CMI higher than 0.2 was recorded in the kidney samples of fetuses younger than the 20th gestational week (GW), while a value lower than 0.1 was recorded in the samples older than the 30th GW. With an increase in GA in all zones of the renal cortex, RCa and GCTa decreased. A statistically significant reduction of GCTa was observed in the oldest group in the juxtamedullary and intermediate zones of the cortex (p < 0.01). Glomeruli located in the deeper parts of the cortex were more mature than the superficial ones. Conclusion. The measured parameters can serve as a starting point for future studies that would analyze the histomorphological characteristics of the fetal kidney cortex. In the absence of clinical data, a newly formed parameter CMI can represent assistance with the determination of GA, as it significantly correlates with GA (p < 0.01).